RECOGNIZING THE ROLE OF FARMERS IN INDIA'S ECONOMIC SUCCESS FOR FINANCIAL WELL-BEING - Vishwa Suresh; Kumar Bharat (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This research article aims to shed light on the pivotal role played by farmers in India's economic success. Through a comprehensive review and analysis of existing literature, policy documents, and statistical data, this study examines the socioeconomic contributions of farmers, evaluates policy frameworks, investigates challenges faced by farmers, and proposes strategies for their empowerment. The findings highlight the multifaceted contributions of farmers to the Indian economy, including agricultural production, employment generation, rural development, and poverty alleviation. Additionally, the study assesses the effectiveness of existing policies and institutional frameworks in supporting farmers' economic role, identifying areas for improvement. It also delves into the challenges and constraints faced by Indian farmers, ranging from limited access to credit and land tenure issues to market volatility and climate change impacts. Based on the analysis, this article proposes strategies for empowering and promoting the economic well-being of Indian farmers. These strategies encompass technological advancements, agricultural diversification, farmer collectives, market linkages, and policy reforms. By recognizing and addressing the barriers hindering farmers' economic progress, the article argues that India can unlock the full potential of its agricultural sector, foster rural development, and achieve sustainable economic growth.